Architecting Vue.js 3 enterprise-ready web applications build and deliver scalable and high-performance, enterprise-ready applications with Vue and JavaScript - Eseme, Solomon (Packt Publishing Ltd., 2023)
Building enterprise-ready Vue.js apps entails following best practices for creating high-performance and scalable applications. Complete with step-by-step explanations and best practices outlined, this Vue.js book is a must-read for any developer who works with a large Vue.js codebase where performance and scalability are indispensable. Throughout this book, you'll learn how to configure and set up Vue.js 3 and the composition API and use it to build real-world applications. You'll develop the skills to create reusable components and scale performance in Vue.js 3 applications. As you progress, the book guides you in scaling performance with asynchronous lazy loading, image compression, code splitting, and tree shaking. Furthermore, you'll see how to use the Restful API, Docker, GraphQL, and different types of testing to ensure that your Vue.js 3 application is scalable and maintainable. By the end of this book, you'll be well-versed in best practices for implementing Restful API, Docker, GraphQL, and testing methods to build and deploy an enterprise-ready Vue.js 3 application of any scale.